Interactive skeleton - Abrahams, Peter H. (London : Primal Pictures, 1998)
Interactive skeleton is a complete, accurate 3-D human skeleton, showing every detail, muscle attachment, and landmark. The disc comes comes complete with comprehensive revision aids. It is a key educational resoure in medicine , anatomy, surgery, and allied heath fields
Title from disc label
System requirements: PC Windows 3.1 go to Program Manager. Under file choose run. Type d
Keywords: Skeleton